Effective Technological Schemes for the Cultivation of Industrial Open-Earth Vineyards in the Don Area - Shamil , Huseynov; Sergey, Mayborodin (KnE Life Sciences, 2021)
Over the long years of the development of agro-technological approaches to the methods of grape growing, researchers paid special attention to the issues of pruning grape bushes, the methods of their formation and maintenance and planting plans. In the environmental conditions of the Lower Don of the Russian Federation, many years of research were conducted in order to establish the optimal parameters of various agro-technological methods used in the vineyard (the methods of maintaining, forming, pruning and the rates of bush loading) through the example of a promising variety of Crystal grapes of interspecific origin. At the same time, a prerequisite for this research was the link with the scheme of planting vines and its effect on the productivity of uncultivated vineyards, as well as the quality of the crop. In this study, we proposed the technological and economic advantages of industrial and intensive methods of maintaining and forming vineyards on an industrial basis. These methods were new for the Don conditions. We conducted research and studied various ways of maintaining, forming, pruning and loading grape bushes in the Rostov Region, in the conditions of the experimental field, which increased the use of photosynthetic active radiation (PAR) in the production process on standard open-earth vineyards of industrial and intensive type, when cultivating Crystal grape varieties of interspecific origin. Processing and analysis of the results of the application of various agricultural methods in the experimental areas will reveal the most optimal ones from an economic point of view. Keywords: grapes, architectonics, management method, productivity, biomass